2016
DOI: 10.1016/j.knee.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

TT-TG vs. modified lateral patellar edge for determination of tibial tubercle transfer distance in Fulkerson osteotomy procedures

Abstract: Background: Tibial tubercle-trochlear groove (TT-TG) distance is currently used at our institution to determine tibial tubercle medialization required in Fulkerson osteotomies. If the correlation between a modified lateral patellar edge (LPE) and the transfer distance was found to be stronger than its correlation with TT-TG, it would suggest that the best measurement to use is actually modified LPE. Methods: The electronic medical records of 32 patients who underwent Fulkerson osteotomy procedures with femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The second-most reported measurement in the patellar tracking category was the congruence or Merchant angle (13 studies). ¶ Five of 6 studies (83%) that measured TT-TG distance using CT 22,44,55,77,106,112 and 9 of 15 study populations (13 studies) # (60%) that measured TT-TG distance using MRI reported interobserver ICCs >0.9. ** However, all studies reported interobserver ICCs >0.75 for TT-TG distance, regardless of imaging modality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second-most reported measurement in the patellar tracking category was the congruence or Merchant angle (13 studies). ¶ Five of 6 studies (83%) that measured TT-TG distance using CT 22,44,55,77,106,112 and 9 of 15 study populations (13 studies) # (60%) that measured TT-TG distance using MRI reported interobserver ICCs >0.9. ** However, all studies reported interobserver ICCs >0.75 for TT-TG distance, regardless of imaging modality.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, planning for bony realignment procedures involving tibial tubercle osteotomy has found good utility in patellar tracking measurements, including the TT-TG distance. 44 It should be noted, however, that the predictability of the static TT-TG measurement related to dynamic patellar tracking has been brought into question. 24 The present study sought to categorize the 106 unique measurements identified in the literature as a way to qualitatively organize this information for clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations